2010
DOI: 10.1227/01.neu.0000372225.37968.29
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Giant Basilar Artery Aneurysm With a Bridging Stent and Subsequent Coil Occlusion of the Stent

Abstract: The patient experienced immediate total occlusion of the aneurysm with almost total recuperation after 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Recently, Jones et al [ 21 ] and Wenderroth et al [ 22 ] have published their cases describing successful endosaccular treatment of giant BA aneurysm with BA trunk occlusion. Endovascular BA occlusion alone without aneurismal packing for blood flow reversal is one alternative treatment for geometrically difficult vertebrobasilar aneurysms either through unilateral or bilateral VA occlusion or selective BA occlusion [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jones et al [ 21 ] and Wenderroth et al [ 22 ] have published their cases describing successful endosaccular treatment of giant BA aneurysm with BA trunk occlusion. Endovascular BA occlusion alone without aneurismal packing for blood flow reversal is one alternative treatment for geometrically difficult vertebrobasilar aneurysms either through unilateral or bilateral VA occlusion or selective BA occlusion [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the 35 cases reported in the literature in which there is a somewhat detailed description of the placement of cerebral vascular scaffolds in children, we found that antiplatelet administration for endovascular treatment was extremely variable (On-line Table 2). [2][3][4][5][6][7][8][9][10][11]25,[31][32][33][34][35][36][37][38][39][40][41][42][43] There are neither guidelines published on antiplatelet therapy (APT) in children with cerebrovascular diseases 25 nor conclusive trials on pediatric APT regimens. 44,45 Weight-based dose calculations extrapolated from an adult dosing of 75 mg per day are not only misleading but also may lead to lifethreatening consequences.…”
mentioning
confidence: 99%